Pain in the rheumatic patient - Calvo Quiroz, Armando (2024)
The concept of pain in the rheumatic patient is reviewed; this pain has been traditionally considered nociceptive, that is, caused by tissue damage. The importance of chronic pain in these patients is described, and different therapies are discussed; among the non-pharmacological therapies the roles of education, family, and other factors are presented; several pharmacological therapies are discussed, such as acetaminophen, nonsteroidal antiinflammatory drugs (NSAIDs), opioids; a few general principles are defined. An in depth analysis of risk factors to develop gastric complications using NDAIDs and coronary disease with COX-2 inhibitors is provided.